Macrophages in helminth infection - Allen, Judith (Henry Stewart Talks, 2012)
Discovery & functions of macrophages, Th1 and Th2 immunity, Macrophage activation states, Macrophage function in helminth infection, Evolution of Th2 immunity, Macrophages in inflammation, Macrophage proliferation in the tissues during Th2 immunity, New modes of inflammation
Reviewed at 2017/03/08